2016
DOI: 10.1590/1678-4162-8374
|View full text |Cite
|
Sign up to set email alerts
|

Potencial cicatricial da Bixa orellana L. em feridas cutâneas: estudo em modelo experimental

Abstract: 1 Programa de pós-graduação e -FVet  UFPel  Pelotas, RS 2 Faculdade de Veterinária  UFPel  Pelotas, RS 3 Centro de Ciências Químicas, Farmacêuticas e de Alimentos  UFPel  Pelotas, RS  RESUMO O uso de fitoterápicos é uma alternativa de baixo custo e de fácil acesso para o tratamento de feridas cutâneas. Objetivou-se avaliar a ação do extrato oleoso de urucum na cicatrização de feridas cutâneas abertas. Inicialmente, identificaram-se os principais ácidos graxos do óleo de urucum. Foi realizado ensaio cito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
3
0
9
Order By: Relevance
“…The results of this study, both qualitative and quantitative, showed that the acute inflammatory process in the control group was heightened compared to that in the membrane group, thus showing the anti-inflammatory effects of the PHB membrane with norbixin. A study by Capella et al 23 showed the significant proinflammatory activity of an annatto (Bixa orellana L.) oily extract, which was associated with a favorable outcome with respect to the healing process of epithelial injury and a lower inflammatory density on day 7 compared that in the other groups. This was due to the fatty acids (linoleic and oleic) contained in the preparation, which have chemotactic properties for poly and mononuclear cells, accelerating the healing process, as shown by increased scar formation and faster epithelialization.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The results of this study, both qualitative and quantitative, showed that the acute inflammatory process in the control group was heightened compared to that in the membrane group, thus showing the anti-inflammatory effects of the PHB membrane with norbixin. A study by Capella et al 23 showed the significant proinflammatory activity of an annatto (Bixa orellana L.) oily extract, which was associated with a favorable outcome with respect to the healing process of epithelial injury and a lower inflammatory density on day 7 compared that in the other groups. This was due to the fatty acids (linoleic and oleic) contained in the preparation, which have chemotactic properties for poly and mononuclear cells, accelerating the healing process, as shown by increased scar formation and faster epithelialization.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Este ensaio nos possibilitou a observação da toxicidade gerada pelo extrato aquoso de W. douradinha quando em contato direto com células, em ambas linhagens. A incorporação do corante pelas células foi lida e demonstrada em valores de absorbância por espectrofotômetro de placas, os índices demonstrados pela coluna controle foram adotados como padrão 100%, índices superiores a 90% adotados como não citotóxicos, conforme padronizados anteriormentes (CAPELLA et al, 2016). Foram utilizadas concentrações a partir de 10% (dose máxima) seguindo uma sequência de diluições até 0,0001%.…”
Section: Efeito Citotóxicounclassified
“…Além dessas plantas, estudos apontam potencial ação cicatrizante de extratos de urucum em feridas abertas, com efeito pró-inflamatório e indutor de angiogênese (Santos et al, 2014;Sharma & Roy, 2014;Capella et al, 2016). E, também, a ação de extratos de trigo como um estimulante da fibroplasia (Tillmann et al, 2014;Sanguigno et al, 2015;.…”
Section: Introductionunclassified